Pengaruh Model Kooperatif Take and Give Terhadap Hasil Belajar Tematik Tema Daerah Tempat Tinggalku Siswa Kelas IV SD Swasta Al Washliyah Sei Rampah - Khairuna Khairuna; Sujarwo Sujarwo (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
This study aims to examine the effect of the take and give cooperative model on student learning outcomes. The pre-test was conducted on both groups, namely the experimental group that received treatment and the control group that did not receive treatment, to measure students’ initial understanding before treatment was given. The pre-test results showed that both groups had not reached the specified Minimum Completion Criteria (KKM). After that, treatment with the take and give model was carried out in the experimental group, while the control group did not receive treatment. The post-test was conducted after the treatment to measure learning outcomes after the treatment was given. Data analysis using SPSS showed a significant difference between students’ learning outcomes on the pre-test between the experimental group and the control group, indicating a difference in students’ initial understanding between the two groups. The post-test results showed that the experimental group achieved significant improvement and reached the specified KKM, while the control group still did not reach it. This finding shows that the take and give cooperative model has a significant effect in improving student learning outcomes in the experimental group. However, the difference in learning outcomes before and after treatment in the control group was not statistically significant, indicating that the control group did not experience a significant improvement in student learning outcomes. Thus, it can be concluded that the take and give cooperative model is effective in improving student learning outcomes. This study provides support for the use of this model in relevant learning contexts. Suggestions include the application of this model in learning, the development of learning strategies that involve student interaction, regular monitoring and evaluation, further research with a larger sample size, and the development of students’ cooperative skills.